Bisphenol A exposure, interaction with genetic variants and colorectal cancer via mediating oxidative stress biomarkers. (15th October 2021) - Deng, Yao; He, Heng; Wan, Hao; Shen, Na; Li, Jiaoyuan; Zhang, Shanshan; Zeng, Qiang; Chang, Jiang; Lu, Qing; Zhong, Rong; Miao, Xiaoping
Abstract: Bisphenol A (BPA) may induce oxidative stress as well as the toxicity of colon cancer cells. We hypothesized that BPA exposure and interactions with genetic variants might be associated with colorectal cancer (CRC) risk, and the association might be partly mediated by oxidative stress. We measured urinary BPA and three oxidative stress markers [8-iso-prostaglandinF2α (8-isoPGF2α ), 8-hydroxydeoxyguanosine (8-OHdG) and 4-hydroxy-2-nonenal-mercapturic acid (HNE-MA)] in 275 new CRC cases and 538 healthy controls. A set of 25 genetic variations in 12 candidate DNA repair genes and 5 metabolic enzyme genes were genotyped by Sequenom MassARRAY approach. In multivariable logistic regression, significant positive associations of CRC risk with BPA, 8-OHdG and HNE-MA were observed. Additionally, 8-OHdG, HNE-MA and 8-isoPGF2α were significantly positively associated with BPA ( P  < 0.05). The mediation analysis showed BPA-associated HNE-MA significantly mediated 11.81% of the effect of BPA on CRC risk. Moreover, BPA was found to interact with ERCC5 rs17655 and rs2296147 (both P multiplicative  < 0.05) to increase CRC risk. In brief, our results suggested BPA was associated with CRC risk and the positive association of BPA with CRC risk might be partly mediated by the oxidative stress HNE-MA. BPA might interact with ERCC5 rs17655 and rs2296147 to increase CRC risk. Graphical abstract: Image 1 Highlights: Bisphenol A (BPA) was positively associated with three oxidative stress biomarkers and the risk of colorectal cancer. Oxidative stress biomarker HNE-MA significantly mediated 11.81% of the effect of BPA on colorectal cancer risk. BPA was found to interact with ERCC5 rs17655 and rs2296147 to increase colorectal cancer risk.